ESTRATÉGIAS DE COMUNICAÇÃO ORGANIZACIONAL DIGITAL: O ESTUDO DE CASO DA EMBRAPA - Ribeiro, Maria Eugênia (2014)
With the advent of internet and its subsequent use as a means of communication, it is necessary to know, through analysis of literature on communication and internet, as well as empirical observation of the digital environment, what opportunities for improvement in processes of organizational communication open from the incorporation of internet usage (media and social networks) communication strategies of the institutions. The study aims to analyze the process of insertion of Embrapa in the environment of the media and social networks, what strategies the company used to prepare its institutional entrance in this ecosystem and how it utilizes the digital organizational communication strategies to promote its actions and strengthen relationships with its stakeholders. Furthermore, this text will discuss strategy models and the importance of planning (with setting goals, defining public) and monitoring when it intends to operate in the digital environment in a strategic way. The method consists of a case study which will assess the performance of Embrapa in the social network Facebook, through literature review, desk research, content analysis and semi-structured interviews.